PERÍCIA PSICOLÓGICA E VIOLÊNCIA SEXUAL INFANTIL: conhecendo a atuação dos psicólogos no Maranhão - GAMBA, Moara de Oliveira (2015)
In addition to the various theoretical schools Psychology that are with different views of man and world we also find various fields of activity of the psychologist. Such fields has been expanding and specializing from the dialogue with other knowledge. In this job highlight one of the insertion of this professional areas on the rise in Brazil, the Forensic Psychology, specifically, the work of the psychologist in the psychological expertise with child victims of sexual violence. The main purpose of this study, therefore, is to meet the practice of Psychological Expertise involving child victims of sexual violence in State of Maranhão from the perception of professionals of psychology, identifying still the insertion of the psychologist and the dialogue between law and Psychology in this context. It is a historical documentary research in the 1990-2014 period with unstructured interviews analyzed from the method phenomenological Psychology research proposed by Giorgi (2008). To achieve the goals outlined, the research was based on studies of the history of psychology, Forensic Psychology in Brazil, brazilian legislation and criminal law. Among the main results in the analysis of the narratives we highlight the procedures adopted by the psychological expertise, recognized as pioneers in Brazil, the need of expansion of number of professionals and qualification of the same and the criticism of the "Testimony without damage. Thus the considerations presented are relevant to the emergence of new studies and reflections on the subject.